steilbergauf wrote:

Bunnuel, I have a hard time getting my approach clear on problems like that.

What made you rearrange statement (1) and not insert it in the q stem such as (2x)(x+y)?

well you just have to recognise that we are dealing with a differences of squares, thats it.

x^2-y^2 =

(x-y) (x+y)

Even if you get statement one wrong, statement 2 will safe your ass

For instance:

(1) x+y=2x

lets say insufficient

(2)

x-y=0 now you should recognise where this is going,

so lets go back to

(1) x+y=2x

0 = 2x-x-y

0 = x-y--> sufficient

_________________

I hate long and complicated explanations!